A Spread Spectrum Sequence for MC-CDMA System - Zhicheng Zhang; Xiaona Huang; Li Xiong (Dianxin kexue)
The MC-CDMA system takes the advantages of the OFDM system and the CDMA system.The MC-CDMA system is a kind of wireless communication aroused an ongoing and growing research interests,which has the characteristics of high bit transmission rate,high bandwidth efficiency,anti-jamming,and a large system capacity.Since the MC-CDMA system includes the multi-carrier modulation,it is difficult to design a spread spectrum sequence performing not only a high level of self-correlation and cross-correlation but also a low peak-to-average power ratio in the MC-CDMA system.To solve this problem,a spread spectrum sequence which was modulated by Golay code and m sequence was proposed.The spread spectrum sequence proposed owned a good performance in self-correlation,cross-correlation and peak-to-average power ratio.The simulation results show the effectiveness and the superiority of the proposed spread spectrum sequence.